Improving the usefulness of mortality data: reclassification of ill-defined causes based on medical records and home interviews in Brazil - França,Elisabeth Barboza (2019)
ABSTRACT Introduction: Brazil presented a high proportion of ill-defined causes of death (IDCD) in 2000, compromising accurate cause-of-death analysis. Objective: To analyze specific underlying causes for deaths originally assigned as IDCD in the Mortality Information System (SIM - Sistema de Informação sobre Mortalidade), after investigation activities implemented in country between 2006 and 2017. Method: For all IDCD identified in the SIM, municipal health professionals collected information about the final disease obtained from hospital records, autopsies, forms of family health teams, and home investigation. Specific causes among reclassified IDCD after investigation were evaluated according to age groups and four calendar periods. Results: Proportions of IDCD reassigned to other causes after review increased over time, reaching 30.1% in 2017. From a total of 257,367 IDCD reclassified in 2006-2017, neonatal-related conditions, injury, ischemic heart disease and stroke were the leading causes detected in the age groups 0-9 years, 10-29 years, 30-69 years, 70 years and over, respectively. Discussion: The similarity and plausibility of cause-specific proportions derived from the reclassification of IDCD by age group over time indicate the accuracy of the investigation data. Conclusion: High proportions of IDCD reassigned to more informative causes after review indicate the success of this approach to correct misclassification in the SIM, an initiative that should be maintained. Training physicians on death certification along with better quality of medical care and access to health services would lead to further improvement.